Interplatform reproducibility of liver and spleen stiffness measured with MR elastography. Issue 5 (15th October 2015) - Yasar, Temel Kaya; Wagner, Mathilde; Bane, Octavia; Besa, Cecilia; Babb, James S.; Kannengiesser, Stephan; Fung, Maggie; Ehman, Richard L.; Taouli, Bachir
Abstract : Purpose: To assess interplatform reproducibility of liver stiffness (LS) and spleen stiffness (SS) measured with magnetic resonance elastography (MRE) based on a 2D gradient echo (GRE) sequence. Materials and Methods: This prospective Health Insurance Portability and Accountability Act (HIPAA)‐compliant and Institutional Review Board (IRB)‐approved study involved 12 subjects (five healthy volunteers and seven patients with liver disease). A multislice 2D‐GRE‐based MRE sequence was performed using two systems from different vendors (3.0T GE and 1.5T Siemens) on the same day. Two independent observers measured LS and SS on confidence maps. Bland–Altman analysis (with coefficient of reproducibility, CR), coefficient of variability (CV), and intraclass correlation (ICC) were used to analyze interplatform, intra‐ and interobserver variability. Human data were validated using a gelatin‐based phantom. Results: There was excellent reproducibility of phantom stiffness measurement (CV 4.4%). Mean LS values were 3.44–3.48 kPa and 3.62–3.63 kPa, and mean SS values were 7.54–7.91 kPa and 8.40–8.85 kPa at 3.0T and 1.5T for observers 1 and 2, respectively. The mean CVs between platforms were 9.2%–11.5% and 13.1%–14.4% for LS and SS, respectively, for observers 1 and 2. There was excellent interplatform reproducibility (ICC >0.88 and CR <36.2%) for both LS and SS, and excellent intra‐ and interobserver reproducibility (intraobserver: ICC >0.99, CV <2.1%, CR <6.6%; interobserver: ICC >0.97, CV and CR <16%). Conclusion: This study demonstrates that 2D‐GRE MRE provides platform‐ and observer‐independent LS and SS measurements. J. Magn. Reson. Imaging 2016;43:1064–1072.